2009
DOI: 10.1094/pdis-93-1-0107a
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Pepper veinal mottle virus in Tomato and Pepper in Taiwan

Abstract: In May of 2006, samples from tomato plants (Solanum lycopersicum cv. Known-you 301) exhibiting necrotic symptoms on stems, petioles, and leaves were collected from Chiayi County, Taiwan. Double-antibody sandwich-ELISAs were performed using Cucumber mosaic virus, Tomato mosaic virus, Potato virus Y, Watermelon silver mottle virus, and Chilli veinal mottle virus (ChiVMV) polyclonal antibodies. Three of eight samples reacted with antibodies against ChiVMV but not with the others. Using the potyvirus degenerate pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Tomato cultivation in Taiwan suffers from numerous insect-borne viruses, including potato virus Y (PVY) [3], chilli veinal mottle virus (ChiVMV) [4], pepper veinal mottle virus (PVMV) [5], pepper mottle virus (PepMoV) [6], and tobacco vein banding mosaic virus (TVBMV) [7] of the aphid-transmitted genus Potyvirus in the family Potyviridae. Viruses belonging to the genus Potyvirus have a monopartite, single-stranded positive-sense RNA genome of about 10 kb, encapsidated by multiple units of a single type of coat protein (CP) in flexuous and filamentous particles of 720-850 nm long and 12-15 nm in diameter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tomato cultivation in Taiwan suffers from numerous insect-borne viruses, including potato virus Y (PVY) [3], chilli veinal mottle virus (ChiVMV) [4], pepper veinal mottle virus (PVMV) [5], pepper mottle virus (PepMoV) [6], and tobacco vein banding mosaic virus (TVBMV) [7] of the aphid-transmitted genus Potyvirus in the family Potyviridae. Viruses belonging to the genus Potyvirus have a monopartite, single-stranded positive-sense RNA genome of about 10 kb, encapsidated by multiple units of a single type of coat protein (CP) in flexuous and filamentous particles of 720-850 nm long and 12-15 nm in diameter.…”
Section: Introductionmentioning
confidence: 99%
“…PVMV was first found in Taiwan in 2006 [5] and has become the most prevalent potyvirus infecting tomato and pepper crops in Taiwan [32]. Previous reports have shown that nitrite treatment is suitable for the attenuation of potyviruses [25,33].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in recent years ChiVMV, PVMV, CMV and PMMoV were speculated to become the dominant viruses damaging pepper plants in South China . It's worth noting that ChiVMV and PVMV both belonging to genus Potyvirus in the family Potyviridae were reported on pepper for the rst time in China no more than tweenty years ago (Wang et al 2006;Cheng et al, 2009). Since then, they have spread rapidly in many other pepper growing areas, such as Hunan (Zhang et al, 2016), Yunan (Rao et al, 2020), etc.…”
Section: Introductionmentioning
confidence: 99%
“…This virus is well documented of infected pepper crops in several countries in Africa [ 10 , 11 ], and the phylogenetic relationship among different isolates with CP gene level has been extensively studied [ 9 ]. In Asia, this virus was reported infecting pepper crops in India and Taiwan [ 12 ]. However, as our best knowledge, there is no complete genome RNA sequence of PVMV infecting pepper crops in mainland China so far.…”
Section: Introductionmentioning
confidence: 99%